PENGATURAN HUKUM PENCATATAN PERKAWINAN ANTAR AGAMA DI INDONESIA - Chairulsyah, Muhammad Octaris; Kamarullah, Kamarullah (Tanjungpura Legal Review, 2024)
Abstract  This research is entitled "Judicial Study of Marriage Registration between People of Different Religions in Indonesia" with a problem formulation of how to regulate the registration of marriages between people of different religions in Indonesia? And the goal is to find out and analyzing the arrangements for registering marriages between people of different religions in Indonesia. The research method used is a normative research method with the data used in the form of primary, secondary and tertiary legal materials. The results of this research show that the registration of marriages between people of different religions in Indonesia is regulated in various existing regulations. The first is regulated in Article 35 Letter (a) of the Adminduk Law which states that the registration of marriages as intended in Article 34 also applies to marriages determined by the Court and the explanation of the article states that what is meant by a marriage determined by the court is a marriage between people of different religions. Secondly, it is regulated in Article 50 Paragraph (3) PERMENDAGRI NO 108 TH 2019 which states that in the case of marriages between people of different religions and marriages that cannot be proven by a marriage certificate, marriage registration is carried out based on a court order by fulfilling the requirements, one of which is is a copy of the court order. And finally, it is regulated in SEMA NO 2 TH 2023 which requires judges to be guided by the SEMA in adjudicating cases of requests for registration of marriages between people of different religions and beliefs and in one of the points it says that the court does not grant requests for registration of marriages between people of different religions. and trust.AbstrakPenelitian ini berjudul "Kajian Yuridis Pencatatan Perkawinan Antar-Umat Berbeda Agama Di Indonesia" dengan rumusan masalah bagaimana pengaturan pencatatan perkawinan antar-umat berbeda agama di Indonesia? Dan tujuannya yaitu untuk mengetahui dan menganalisis pengaturan pencatatan perkawinan antar-umat berbeda agama di Indonesia. Metode penelitian yang digunakan yakni metode penelitian normatif dengan data yang digunakan   berupa bahan hukum primer, sekunder dan tersier. Hasil penelitian ini menunjukkan bahwa pencatatan perkawinan antar-umat berbeda agama di Indonesia diatur di berbagai regulasi yang ada. Yang pertama diatur di dalam Pasal 35 Huruf (a) UU Adminduk yang mengatakan bahwa pencatatan perkawinan sebagaimana yang dimaksud didalam Pasal 34 berlaku pula bagi perkawinan yang di tetapkan oleh Pengadilan dan penjelasan pasal tersebut mengatakan bahwa yang dimaksud dengan perkawinan yang ditetapkan oleh pengadilan adalah perkawinan   antar-umat yang berbeda agama. Yang kedua, diatur didalam Pasal 50 Ayat (3) PERMENDAGRI NO 108 TH 2019 yang mengatakan bahwa dalam hal perkawinan antar-umat yang berbeda agama dan perkawinan yang tidak dapat dibuktikan dengan akta perkawinan, pencatatan perkawinan dilaksanakan berdasarkan penetapan pengadilan dengan memenuhi persyaratan yang salah satunya adalah salinan penetapan pengadilan. Dan yang terakhir, diatur didalam SEMA NO 2 TH 2023 yang mengharuskan hakim untuk unutk berpedoman pada SEMA tersebut dalam mengadili perkara permohonan pencatatan perkawinan antar-umat ynag berbeda agama dan kepercayaan   dan di salah satu poinnya mengatakan pengadilan tidak mengabulkan permohonan pencatatan perkawinan antar-umat yang berbeda agama dan kepercayaan.